Turkey - (:unkn) unknown (My University, 1989)
"In this review of educational policy in Turkey, the examiners were asked to consider the education system as a whole excluding higher education as such but not teacher training ... On the functioning of the education system as a whole the examiners perceive several priority needs and offer suggestions for dealing with them: greater co-ordination of educational policies with other national policies; ensuring that quantitative expansion does not lead to significant qualitative decline and regional imbalances; devolving responsibilities and powers to the regional and local level; improving the structure and professional competency of the Ministry of Education; strengthening research and development capacity; devising effective instruments for monitoring the system." (author's abstract) In dem OECD-Gutachten werden Bildungspolitik, Bildungsplanung und Bildungsfinanzierung in der Türkei untersucht und bewertet und Reformansätze auf verschiedenen Ebenen im Schul- und Berufsausbildungsbereich und in der Lehrerbildung analysiert. Nicht eingeschlossen ist das Hochschulwesen. (IAB)
Keywords: S 2.3 Berufsbildungspolitik; S 1 Stufen der Berufsbildung; S 1.1 Allgemeinbildende Schule; P 3.2.3 Lehrer; Bildungspolitik; Bildungssystem; Schulwesen; Berufsbildendes Schulwesen; Bildungsreform; Lehrer; Berufsausbildung; Berufsproblem; Betriebliche Berufsausbildung; Quantitative Angaben